Patient Satisfaction with Orthodontic Treatment and Associated Factors - Tahmasbi, Soodeh; Namdari, Mahshid; Ziaei, Mohsen (Journal of Dental School, 2019)
Objectives This study evaluated the satisfaction of patients receiving orthodontic treatment and the related factors probably affecting their level of satisfaction. Methods In this cross-sectional study, 193 patients who had finished their orthodontic treatment at the Department of Orthodontics of Shahid Beheshti Dental School, completed a researcher-made questionnaire on satisfaction with the process of treatment, treatment outcomes and its psychosocial benefits. The validity and reliability of the questionnaire were first verified. Descriptive statistics, t-test, one-way ANOVA and Pearson’s correlation test were used to assess the level of patient satisfaction, and the effects of gender, age, type of malocclusion, and type and duration of treatment on the level of satisfaction. Level of significance was set at 0.05. Results The frequency of patients who were highly satisfied with the final alignment of their teeth, esthetic facial appearance and smile attractiveness was 62.7%, 50.8% and 63.7%, respectively. Respondents gave the highest satisfaction score to smile attractiveness (1.62±0.53) and alignment of their teeth (1.61± 0.52) and the lowest score to the postgraduate student’s professional skills (0.79± 0.54). The mean total satisfaction score was 1.36 out of 2, which indicated that patient satisfaction with the orthodontic treatment was relatively high. Duration of treatment showed a weak (r=0.186) but significant (P=0.011) correlation with the level of satisfaction. Conclusion Generally speaking, patient satisfaction with the health services provided in the Department of Orthodontics of Shahid Beheshti Dental School was relatively high. No correlation was found between patient satisfaction and gender, type of malocclusion or type of treatment